Letter to Jane Tolmach from Joe A. Gonsalves - Joe A. Gonsalves:::::: (1970)
In this November 20, 1970 letter, Assemblyman Joe A. Gonsalves thanks Jane Tolmach for informing him about the Key Women Award Party honoring volunteer workers. He encloses a list of names of women to be recognized for their campaign contributions.